Elastofibroma: a rare entity - P. Singh, Lokesh; Jain, Sanchit; Mural, Anupam; Kumar, Sumeet (International Journal of Research in Orthopaedics, 2026)
Elastofibroma dorsi is a rare, benign soft-tissue pseudotumor that typically arises in the infrascapular region of elderly individuals. Due to its deep location and firm consistency, it may clinically and radiologically mimic malignant soft-tissue tumors, leading to diagnostic uncertainty. We report the case of a 57-year-old male who presented with a gradually enlarging, painful swelling in the right infrascapular region, associated with mechanical discomfort during shoulder movements. Clinical examination revealed a poorly defined, non-tender mass beneath the inferior border of the scapula. Imaging studies demonstrated characteristic findings, including a heterogeneous soft-tissue lesion with interspersed fatty streaks on computed tomography and a typical “striated” appearance on magnetic resonance imaging, with bilateral involvement. As the patient was symptomatic on the right side, surgical excision was performed. Histopathological examination confirmed the diagnosis of elastofibroma, showing fibrocollagenous tissue with abnormal elastic fibers and interspersed adipose tissue. The postoperative course was uneventful, with complete symptom resolution and no recurrence at six-month follow-up. Elastofibroma dorsi should be considered in the differential diagnosis of chronic infrascapular swellings, particularly in older patients with mechanical shoulder symptoms. Recognition of characteristic imaging features allows for accurate diagnosis and appropriate management. Surgical excision provides excellent symptomatic relief in selected cases.